P-graph methodology for cost-effective reduction of carbon emissions involving fuel cell combined cycles - Varbanov, Petar; Friedler, Ferenc (Applied thermal engineering, 2008)
Fuel cells are under extensive investigation for building combined energy cycles due to the higher efficiency potential they offer. Two kinds of high-temperature fuel cells (HTFC) have been identified as best candidates for fuel cell combined cycles (FCCC) – molten carbonate fuel cells (MCFC) and solid oxide fuel cells (SOFC). The paper presents a procedure for the evaluation of energy conversion systems involving FCCC subsystems, utilising biomass and/or fossil fuels, providing a tool for evaluation of the trends in CO 2 emission levels and economics of such systems. This involves significant combinatorial complexity, efficiently handled by the P-graph algorithms. Promising system components are evaluated using the P-graph framework and a methodology for the synthesis of cost-optimal FCCC configurations is developed, accounting for the carbon footprint of the various technology and fuel options. The results show that such systems employing renewable fuels can be economically viable for a wide range of economic conditions, mainly due to the high energy efficiency of the FC-based systems.